2022
DOI: 10.1371/journal.pntd.0010199
|View full text |Cite
|
Sign up to set email alerts
|

Larval source reduction with a purpose: Designing and evaluating a household- and school-based intervention in coastal Kenya

Abstract: Background Since Aedes aegypti mosquitoes preferentially breed in domestic containers, control efforts focus on larval source reduction. Our objectives were to design and test the effectiveness of a source reduction intervention to improve caregiver knowledge and behaviors in coastal Kenya. Methodology/Principal findings We conducted a cluster-randomized controlled trial with 261 households from 5 control villages and 259 households from 5 intervention villages. From each household, one child (10–16 years ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Four studies 19 , 20 , 21 , 22 showed a reduction in larval and pupal indices. The three other studies 23 , 24 , 25 showed a trend in intervention areas but did not achieve significant reduction levels.…”
Section: Resultsmentioning
confidence: 84%
“…Four studies 19 , 20 , 21 , 22 showed a reduction in larval and pupal indices. The three other studies 23 , 24 , 25 showed a trend in intervention areas but did not achieve significant reduction levels.…”
Section: Resultsmentioning
confidence: 84%
“…The extent to which these ecological differences imply differences in control strategies should be further evaluated. Meanwhile, we believe that though insightful vector control strategies have been proposed to be applied in HH [ 33 , 43 ], the lack of inclusion of NH environments could lead to a latent risk that continues the transmission cycle at a city level. Unfortunately, we were unable to fit our data from the NH environment in Ukunda into a binomial logistic regression model: possibly due to excessive randomness in the distribution of evaluated risk factors, which could suggest that there are other factors involved that we could not evaluate.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of litter was also associated with being found in a hotspot for all three infections, with the strongest association for malaria [ 41 ]. Plastic containers and other waste can collect rainwater and have been shown to serve as breeding grounds for multiple mosquito species [ 15 , 16 , 23 , 42 45 ]. A recent study in Brazil demonstrated increased seroprevalence of DENV and CHIKV in waste pickers at an open-air landfill [ 46 ].…”
Section: Discussionmentioning
confidence: 99%